1996
DOI: 10.1016/0014-5793(96)00912-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural comparison of a 15 residue peptide from the V3 loop of HIV‐1IIIb and an O‐glycosylated analogue

Abstract: As part of a program to study the effect of glycosylation on the three-dimensional structures of HIV-ImB V3 peptide constructs, we have examined the solution structures of a 15 residue peptide (RIQRGPGRAFVTIGK, P18ms), originally mapped as an epitope recognized by CD8 + D u class I MHC-restricted murine cytotoxic T-lymphocytes (CTL), and an analogue (P18mB-g), O-glycosylated with an t~-galactosamine on Thr-12, using NMR, circular dichroism and molecular modeling methods. Our studies show that the peptides samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 43 publications
(28 reference statements)
3
26
0
Order By: Relevance
“…In principle other noninteractive, noncarbohydrate moieties mounted at the ␥ carboxyl of the asparganine residue might well have induced their own conformational restrictions on the peptide. However, our work in concert with earlier findings (14)(15)(16)(17)(18)(19)(20)(21) tends to suggest the existence of such specific contacts as biasing element in glycopeptides. It has been argued theoretically that a modest change in biasing the energy landscape can have a significant effect on reducing the number of folding paths a protein may choose with concomitant increase in the rate of productive folding (3).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…In principle other noninteractive, noncarbohydrate moieties mounted at the ␥ carboxyl of the asparganine residue might well have induced their own conformational restrictions on the peptide. However, our work in concert with earlier findings (14)(15)(16)(17)(18)(19)(20)(21) tends to suggest the existence of such specific contacts as biasing element in glycopeptides. It has been argued theoretically that a modest change in biasing the energy landscape can have a significant effect on reducing the number of folding paths a protein may choose with concomitant increase in the rate of productive folding (3).…”
Section: Resultssupporting
confidence: 70%
“…In the case of O-linked glycopeptides (14,15,20), NMR studies have shown that the peptide backbone responds to glycosylation, as evidenced by changes in sequential amideamide nuclear Overhauser effect (NOE) interactions. The response is further modulated by whether the sugar component is a mono-or disaccharide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR studies of isolated V3 peptides show no stable structure in solution, but transient turns exist around GPGR (7-9, 17, 18, 19, 25, 33, 36, 37, 52, 64, 77, 79, 80, 84). NMR studies of peptides modified by cyclization (4,9,33,38,74,(76)(77)(78), by replacement of Ala P316 with the conformationally restricted residue ␣-aminoisobutyric acid (4,25), by glycosylation (36,37,52), through attachment to resin beads (40), through attachment to a bacteriophage viral coat protein (39), and through attachment to carrier proteins, such as bovine pancreatic trypsin inhibitor (81) and MUC1 (22), all show an increased ␤-turn propensity around GP GRAF, while V3 peptides attached to filamentous bacteriophage fd viral coat protein pVIII (39) adopt a double-turn structure similar to that observed in the Fab 59.1-peptide crystal structure (25,26).…”
mentioning
confidence: 99%
“…These methods included aminoisobutyric acid substitution (10), insertion into a viral coat protein (23), glycosylation (12)(13)(14), attachment to resin beads (24), cyclization of the peptide (15), and trifluoroethanol addition (14 -19).…”
mentioning
confidence: 99%